First experimental validation of silicon-based sensors for monitoring ultra-high dose rate electron beams - Elisabetta Medina; Elisabetta Medina; Arianna Ferro; Arianna Ferro; Mohammad Abujami; Mohammad Abujami; Aurora Camperi; Matteo Centis Vignali; Emanuele Data; Emanuele Data; Damiano Del Sarto; Damiano Del Sarto; et al. (Frontiers in Physics, 2024)
Monitoring Ultra-High Dose Rate (UHDR) beams is one of the multiple challenges posed by the emergent FLASH radiotherapy. Technologies (i.e., gas-filled ionization chambers) nowadays used in conventional radiotherapy are no longer effective when applied to UHDR regimes, due to the recombination effect they are affected by, and the time required to collect charges. Exploiting the expertise in the field of silicon sensors’ applications into clinics, the medical physics group of the University and INFN Torino is investigating thin silicon sensors as possible candidates for UHDR beam monitoring, exploiting their excellent spatial resolution and well-developed technology. Silicon sensors of 30 and 45 µm active thicknesses and 0.25, 1 and 2 mm2 active areas were tested at the SIT ElectronFlash machine (CPFR, Pisa) on 9 MeV electron beams, featuring a pulse duration of 4 µs, a frequency of 1 Hz, and a dose-per-pulse ranging from 1.62 to 10.22 Gy/pulse. The silicon sensors were positioned at the exit of the ElectronFlash applicator, after a solid water build-up slab, and were readout both with an oscilloscope and with a multi-channel front-end readout chip (TERA08). A response linearity extending beyond 10 Gy/pulse was demonstrated by comparison with a reference dosimeter (FlashDiamond), thus fulfilling the first requirement of a potential application in UHDR beam monitoring.